Penentuan Gaji Pokok Manajer Menengah dengan Metode Point System - Dwi Kurniawan; Arby Syihab; Hendang Setyo Rukmi (Jurnal Teknik Industri, 2012)
One strategy to improve the satisfaction of human resources is to give fair compensation based on the characteristics of the their work. Today in PT Bita Enargon Engineering, all division managers are considered to have the same workload so that they get the same basic wage, even though the workload of each division is not exactly the same. This research will determine the base salary using the point system method. The first step of this method is to conduct a job evaluation to determine the job relative value of each position. The next step is to convert the job relative value to the money value by subsituting the job relative value into a regression equation developed from the result of a survey on the closest competitors. Based on the job relative value, the basic salary for division heads and department heads can be decided.